PENGARUH PERENCANAAN PAJAK, TATA KELOLA PERUSAHAAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA DI BEI - Novida Adarapta (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Earnings management is influenced by various factors. This study aims to analyze the effect of tax planning, corporate governance and deferred tax burden on earnings management. Corporate governance in this study uses managerial ownership. The company used in this study is a banking sector company listed on the Indonesia Stock Exchange by obtaining a secondary data source in the form of financial reports obtained through the site www.idx.co.id. The research method uses quantitative analysis and the sampling method uses purposive sampling while the method data analysis using multiple linear regression analysis. The population in this study were 44 companies from banking sector companies listed on the Indonesia Stock Exchange. The research sample consisted of 14 companies. The results of the study simultaneously showed tax planning, managerial ownership and deferred tax burden have a significant effect on earnings management. While the partial test results show that tax planning has a significant effect on earnings management, managerial ownership has not a significant effect on earnings management and deferred tax expense does not have a significant effect on earnings management.